Solubility and bacterial sealing ability of MTA and root-end filling materials - Camila Galletti ESPIR; Juliane Maria GUERREIRO-TANOMARU; Rubens SPIN-NETO; Gisselle Moraima CHÁVEZ-ANDRADE; Fabio Luiz Camargo Villela BERBERT; Mario TANOMARU-FILHO (University of São Paulo, 2016)
ABSTRACT Objective To evaluate solubility and sealing ability of Mineral Trioxide Aggregate (MTA) and root-end filling materials. Material and Methods The materials evaluated were: MTA, Calcium Silicate Cement with zirconium oxide (CSC/ZrO2), and zinc oxide/eugenol (ZOE). Solubility test was performed according to ANSI/ADA. The difference between initial and final mass of the materials was analyzed after immersion in distilled water for 7 and 30 days. Retrograde cavities in human teeth with single straight root canal were performed by using ultrasonic tip CVD 9.5107-8. The cavities were filled with the evaluated materials to evaluate sealing ability using the bacterial leakage test with Enterococcus faecalis. Bacterial leakage was evaluated every 24 hours for six weeks observing the turbidity of Brain Heart infusion (BHI) medium in contact with root apex. Data were submitted to ANOVA followed by Tukey tests (solubility), and Kruskal-Wallis and Dunn tests (sealing ability) at a 5% significance level. Results For the 7-day period, ZOE presented highest solubility when compared with the other groups (p<0.05). For the 30-day period, no difference was observed among the materials. Lower bacterial leakage was observed for MTA and CSC/ZrO2, and both presented better results than ZOE (p<0.05). Conclusion MTA and CSC/ZrO2 presented better bacterial sealing capacity, which may be related to lower initial solubility observed for these materials in relation to ZOE.